(untitled) (Konferensiyalar | Conferences, 2024)
This study examines how social media impacts the mental health of adolescents. A group of adolescents aged 13-18 participated, completing surveys on their social media usage, mental well-being (including depression, anxiety, and self-esteem), and demographic details. Results highlight a significant correlation between excessive social media use and increased levels of depression, anxiety, and reduced self-esteem among adolescents, even after adjusting for relevant factors. Gender and socioeconomic status also appear to influence these effects. Recommendations include implementing digital literacy programs and fostering open communication to promote responsible online behavior and support adolescent mental health.